2021
DOI: 10.1063/5.0015377
|View full text |Cite
|
Sign up to set email alerts
|

Development of small high-voltage AC power supply for a dielectric barrier discharge plasma actuator

Abstract: A dielectric-barrier discharge plasma actuator (DBDPA) is a promising flow control device that can prevent flow separation around an airfoil using electrical discharges. Miniaturizing the DBDPA power supply remains a crucial technological challenge because its size and weight determine the performance of fluid devices equipped with this type of actuator. In this study, we propose a compact high-voltage AC power supply for a DBDPA intended for installation on small airplanes, including unmanned aerial vehicles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[36]. Reference [38], for example, developed their own power supply and experimentally confirmed its effective control of a plasma actuator for airfoil flows at the lower freestream speed of 5 m/s.…”
Section: Small Hv Power Supply and Pamentioning
confidence: 99%
“…[36]. Reference [38], for example, developed their own power supply and experimentally confirmed its effective control of a plasma actuator for airfoil flows at the lower freestream speed of 5 m/s.…”
Section: Small Hv Power Supply and Pamentioning
confidence: 99%
“…Leading-edge perturbations are also effective when strong three-dimensional effects are present, for example on delta [29,30] and low AR rectangular flatplate wings [31][32][33]. Pulse-modulated dielectric barrier discharge (DBD) plasma actuators are particularly attractive because they are light, low-power, and directly convert electrical power to a fluid-based body force [34][35][36]. However, there is a large range of reduced frequencies at which maximum and post-stall lift enhancements are maximized.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that the DBD plasma actuators suppress the separating flow around an airfoil [10,11], reduce the drag in turbulent boundary layers [12], and control the transition of the laminar-to-turbulent boundary layers on a swept wing [13]. The development of the power supply for active flow control devices in real flight environment conditions [14,15] and the development of fabrication techniques towards the industrial applications [16,17] have been tackled quite recently owing to a significant progress in the research on DBD plasma actuators.…”
Section: Introductionmentioning
confidence: 99%